Protein Nanoparticles: Uniting the Power of Proteins with Engineering Design Approaches. Issue 8 (25th January 2022) - Habibi, Nahal; Mauser, Ava; Ko, Yeongun; Lahann, Joerg
Abstract: Protein nanoparticles, PNPs, have played a long‐standing role in food and industrial applications. More recently, their potential in nanomedicine has been more widely pursued. This review summarizes recent trends related to the preparation, application, and chemical construction of nanoparticles that use proteins as major building blocks. A particular focus has been given to emerging trends related to applications in nanomedicine, an area of research where PNPs are poised for major breakthroughs as drug delivery carriers, particle‐based therapeutics or for non‐viral gene therapy. Abstract : Protein nanoparticles (PNPs) have recently gained significant momentum. Advances in protein engineering combined with precise engineering approaches are poised to propel protein‐based delivery systems to the forefront of nanomedicine. This review summarizes emerging technologies, potential opportunities and current challenges of PNPs.